(untitled) (XXI Century. Spanish Literature and Culture)
This work analyzes the Spanish essay’s most important contributions of 2009. The thematic variety of the essay is evident. The essays achieved provide a balance between high-minded thought and lighthearted entertainment. The article pays special attention to the most important philosophical essays.